Investigation of the performance of a cylindrical hopper and metering device of a carrot seeder - Marvin T. Valentin; Andrzej Białowiec; Davut Karayel; Algirdas Jasinskas; Daniel Ciolkosz; Jeffrey A. Lavarias (Scientific Reports, 2023)
Abstract A carrot seeder that utilizes a cylindrical component serving as both hopper/metering device to deposit seeds precisely into planting beds/hills at a uniform interval along a straight row over a plant bed was developed in this study. The seeder was evaluated at different operating speeds (89, 70, 61, 51, 48, 38, and 34 cm s−1) relative to mean number of seeds planted in each hill, hill center, scattering distance ratio, hill spacing and missed hills. The seeder was able to deposit seeds in each hill ranging from 2.8 to 4.0 at all speeds. The mean hill center and missed hills suggested that the seeder is best operated at speed under 70 cm s−1 with the respective values ranging from 0.9 to 1.6 cm and 0–5.5%. This indicates that number of the seeds dropped per hill was very uniform, which is a good indicator of the seeding performance. The hill center and missed hills at 89 cm s−1 were 3.08 cm and 16.67% respectively were significantly higher than at lower speeds. Other operating performances such as the mean number of seeds deposited in each hill and the distance between hills did not appear to vary with the planting speed. The scattering distance ratios of operating speeds from 34 to 61 cm s−1 were less than 30% and therefore acceptable for hill dropping of carrot seeds.